Emerging trends and cross-country health inequalities in congenital birth defects: insights from the GBD 2021 study - Hanjun Liu; Kebin Chen; Tingting Wang; Xiaorui Ruan; Jianhui Wei; Jiapeng Tang; Liuxuan Li; Jiabi Qin (International Journal for Equity in Health)
Abstract Background Previous studies predominantly focused on single types of congenital birth defects (CBDs) or specific national prevalence. This study adopts a holistic perspective to assess current trends and health inequalities in birth incidence rate of various types of CBDs, providing novel insights to inform public health policy formulation. Methods Global, socio-demographic index (SDI) regional, and country-specific estimates incidence cases and rate at birth of CBDs from 1990 to 2021 were derived from the Global Burden of Disease (GBD) 2021. Joinpoint analysis and autoregressive integrated moving average predictive models were employed to evaluate temporal trends in the birth incidence rate of CBDs for the period 2022–2031. Additionally, analysis of associations and health inequalities were conducted to examine the relationship between SDI and the birth incidence rate of CBDs across countries. Results Globally, the birth incidence rate decreased from 5811.17/100k population in 1990 to 5563.72/100k population in 2021, with low SDI regions recording the lowest rate and cases. Joinpoint analysis revealed a global decrease in the birth incidence rate of CBDs (average annual percentage change, AAPC: -0.14%, 95%CI: -0.15% to -0.12%). The most significant decline was observed in neural tube defects (NTD) (AAPC: -1.35%, 95%CI: -1.42% to -1.28%). However, only birth incidence rate of orofacial clefts (OC) is projected to decrease globally the next decade. Within the five SDI regions, the birth incidence rate of OC is also projected to decrease probably. The analysis revealed negative correlations between congenital heart anomalies (CHA), NTD, and SDI, with NTD showing both absolute and relative health inequalities. Conclusions Despite the general decline in overall birth incidence rate of CBDs, projections suggested a probable increasing trend for all types except OC. This underscores the necessity for enhanced surveillance and intervention measures. Furthermore, the successful prevention policies implemented for NTD could serve as effective models for addressing other types of CBDs, thereby improving the current global situation of CBDs.